Nutritional and environmental contributions to autism spectrum disorders: Focus on nutrigenomics as complementary therapy - Jaureguiberry, María Soledad (2020)
The prevalence of autism spectrum disorders (ASD) has risen sharply in the last 30 years, posing a major public health concern and a big emotional and financial challenge for families. While the underlying causes remain to be fully elucidated, evidence shows moderate genetic heritability contribution, but heavy environmental influence. Over the last decades, modern lifestyle has deeply changed our eating, rest, and exercise habits, while exposure to air, water, and food chemical pollution has increased due to indiscriminate use of pesticides, food additives, adjuvants, and antibiotics. The result is a drastic change in the quality of our energy source input, and an overload for antioxidant and detoxification pathways that compromises normal metabolism and homeostasis. Current research shows high prevalence of food selectivity and/or food allergy among children with autism, resulting in essential micronutrient deficits that may trigger or aggravate physical and cognitive symptoms. Nutrigenomics is an emerging discipline that focuses on genotype-micronutrient interaction, and a useful approach to tailor low risk, personalized interventions through diet and micronutrient supplementation. Here, we review available literature addressing the role of micronutrients in the symptomatology of ASD, the metabolic pathways involved, and their therapeutic relevance. Personalized and supervised supplementation according to individual needs is suggested as a complement of traditional therapies to improve outcome both for children with autism and their families.